Pengaruh Motivasi Belanja Hedonis, Gaya Hidup Berbelanja dan Promosi Penjualan terhadap Pembelian Impulsif pada Konsumen Shopee ID - Muhammad Afif; Purwanto Purwanto (STIE Kertanegara Malang, 2020)
This research was conducted on Shopee ID consumers (Studies in STIE Kertanegara Malang Students). The purpose of this research is to find out the influence of hedonic shopping motivation, shopping lifestyle and sales promotions on impulsive purchases on Shopee ID consumers. The method used is quantitative by collecting, presenting and analyzing data from Shoopee ID consumers using a questionnaire to respondents. Data analysis technique in this research is multiple linear regression to determine the effect simultaneously, partially and dominantly. Based on the results of the study, the influence of hedonic shopping motivation, shopping lifestyles and sales promotions on impulsive purchases on Shopee ID consumers was simultaneously significant (0.00). The influence of hedonic shopping motivation, shopping lifestyle and sales promotion on impulsive purchases on Shopee ID consumers is partially significant X1 (0.00), X2 (0.03) and X3 (0.03). Hedonic shopping motivation are influenced by indicators such as : adventure, social, idea. value and status.